Leaning Into Whole Health: Sustaining System Transformation While Supporting Patients and Employees During COVID-19 - Eileen M Dryden PhD; Rendelle E Bolton MPH, MSW, MA; Barbara G Bokhour PhD; Juliet Wu BS; Kelly Dvorin PsyD; Lauri Phillips BS, RDN, LD; Justeen K Hyde PhD (SAGE Publishing, 2021)
Background The US Veterans Health Administration (VA) is transforming its healthcare system to create a Whole Health System (WHS) of care. Akin to such reorganization efforts as creating patient-centered medical homes and primary care behavioral health integration, the WHS goes beyond by transforming the entire system to one that takes a proactive approach to support patient and employee health and wellness. The SARS-CoV-2 pandemic disrupted the VA's healthcare system and added stress for staff and patients, creating an exogenous shock for this transformation towards a WHS. Objective We examined the relationship between VA's WHS transformation and the pandemic to understand if transformation was sustained during crisis and contributed to VA's response. Methods Qualitative interviews were conducted as part of a multi-year study of WHS transformation. A single multi-person interview was conducted with 61 WHS leaders at 18 VA Medical Centers, examining WH transformation and use during the pandemic. Data were analyzed using rapid directed content analysis. Results While the pandemic initially slowed transformation efforts, sites intentionally embraced a WH approach to support patients and employees during this crisis. Efforts included conducting patient wellness calls, and, for patients and employees, promoting complementary and integrative health therapies, self-care, and WH concepts to combat stress and support wellbeing. A surge in virtual technology use facilitated innovative delivery of complementary and integrative therapies and promoted continued use of WH activities. Conclusion The pandemic called attention to the need for healthcare systems to address the wellbeing of both patients and providers to sustain high quality care delivery. At a time of crisis, VA sites sustained WH transformation efforts, recognizing WH as one strategy to support patients and employees. This response indicates cultural transformation is taking hold, with WH serving as a promising approach for promoting wellbeing among patients and employees alike.